2014 International Conference on ICT for Smart Society (ICISS) 2014
DOI: 10.1109/ictss.2014.7013183
|View full text |Cite
|
Sign up to set email alerts
|

Business-IT Alignment: Strategic Alignment Model for healthcare (case study in hospital bandung area)

Abstract: Alignment of the business and IT strategies of organization required to achieve business goals. Business IT Alignment approach via communication, consider the dimensions of organizational culture, top management support and vision implementation as key success factor. Unified Strategic Alignment Model aims to improving understanding of strategic alignment business and IT, consist of business strategy, IT strategy, IT infrastructure and process, organization infrastructure and process. This paper proposed a mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Nonetheless, due to increasing IT expenditures and the enormous amounts of under-utilised, complex data, the healthcare sector needs more efficient practices, research and tools to analyse and maximise the utility of big data (Chawla & Davis, 2013;Guo & Chen, 2023). Health-IT researchers highlight the importance of alignment and a comprehensive approach to the aligning, planning, executing and governing technology components in the healthcare sector (Krey, 2018;Weerasinghe et al, 2018a;Fattah & Arman, 2014).…”
Section: Figure 1 Types Of Big Data In Healthmentioning
confidence: 99%
“…Nonetheless, due to increasing IT expenditures and the enormous amounts of under-utilised, complex data, the healthcare sector needs more efficient practices, research and tools to analyse and maximise the utility of big data (Chawla & Davis, 2013;Guo & Chen, 2023). Health-IT researchers highlight the importance of alignment and a comprehensive approach to the aligning, planning, executing and governing technology components in the healthcare sector (Krey, 2018;Weerasinghe et al, 2018a;Fattah & Arman, 2014).…”
Section: Figure 1 Types Of Big Data In Healthmentioning
confidence: 99%
“…Management is the ability and skills to perform an activity, either together or with others in achieving organizational goals [9]. As stated by Frederik W. Taylor that the management principles that must be considered, is; the need to develop knowledge for each task (guidelines motion, implementation of working standards and eligible work condition), the selection of the right employees in accordance with the requirements of employment, the need for training and stimulation, the need to do research and experiment [10].…”
Section: Introductionmentioning
confidence: 99%
“…In a study, antecedents of business and IT were studies and it was found that sharing of domain knowledge, confidence in IT and planning in organizations were the factors for alignment in business and IT [12]. In order to achieve business goals organizations consider business-IT alignment as a major factor and IT as an enabler [30]. It is important to understand in organizations, business and IT executives who have strengths in respective areas always design strategies in isolation and in turn alignment occurs.…”
Section: Introductionmentioning
confidence: 99%